Metal-dependent gene regulation in the causative agent of Lyme disease - Troxell, Bryan; Yang, X Frank (Frontiers in Cellular and Infection Microbiology, 2013)
Borrelia burgdorferi (Bb) is the causative agent of Lyme disease transmitted to humans by ticks of the Ixodes spp. Bb is a unique bacterial pathogen because it does not require iron (Fe2+) for its metabolism. Bb encodes a ferritin-like Dps homolog called NapA (also called BicA), which can bind Fe or copper (Cu2+), and a manganese (Mn2+) transport protein, Borrelia metal transporter A (BmtA); both proteins are required for colonization of the tick vector, but BmtA is also required for the murine host. This demonstrates that Bb's metal homeostasis is a critical facet of the complex enzootic life cycle between the arthropod and murine hosts. Although metals are known to influence the expression of virulence determinants during infection, it is unknown how or if metals regulate virulence in Bb. Recent evidence demonstrates that Bb modulates the intracellular Mn2+ and zinc (Zn2+) content and, in turn, these metals regulate gene expression through influencing the Ferric Uptake Regulator (Fur) homolog Borrelia Oxidative Stress Regulator (BosR). This mini-review focuses on the burgeoning study of metal-dependent gene regulation within Bb.